COMPARACION CITOGENETICA DE DOS POBLACIONES DE THOMASOMYS LANIGER LANIGER (THOMAS 1895) RODENTIA CRICETIDAE, 115 EN LOS PARAMOS DE CRUZ VERDE Y EL VERJON - Ospina De Dulce, Bertha; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
Cell cultures from bone marrow and peripheral blood obtained by cardiac puncture were used to describe the karyotype of the field m o use Tomasomys laniger laniger in two populations found in the areas of Cruz Verde andEl V erjon, Cundinamarca, (Col.). C-banding and Giemsa staining allowed us to ascertain its diploid number 2n=24 with nine pairs of metacentric, two submetacentric and one acrocentric chromosomes; the fundamental number (FN) was 46. The X chromosomes have a heterochromatic markerband in the q arm; pair 10 has conspicuous satcllites and the Y is a large and uni-que acrocentric chromosome equivalent to more than 5% of the total length of the genome. Polymorphism was observed in and between the two populations. Cytogenetic characteristics of Th. laniger lani-ger differ from other species of the genus, and show a great deal of similarities to o"ther cricetids such as Cricetulus griseus.